Mapping and assessment of water erosion in the Ouèd Bou Lajraf basin (Ouèd Inaouène BV) using the PAP/CAR model and GIS tools - Benaissa, Mohamed; Gartet, Jaouad; Sahi, Fouad; Hamdach, Mustapha (Revista de Estudios Andaluces, 2025)
The study of water erosion in the Inaouène sub-watersheds represents a dynamic phenomenon over time, with the change of one or more responsible factors. In the Bou Lajraf watershed, which represents a sub-watershed of Inaouène, the fragility of the soils, the high slopes and the succession of dry years further promote the exposure of the slopes to the degradation of the surface layer, particularly in the upstream part of the watershed. Using the PAP/RAC approach for a descriptive study of water erosion in the Bou Lajraf watershed will provide geomorphological knowledge of the state of the slopes. The approach method adopted, based on the systematic observation of various phenomena in the field. Thus for each type of defined environment making up the watershed, we noted all the morphogenic manifestations. The interpretations are based on the analysis of the elements of the physical and human environment (modes of exploitation of the soil). The qualitative analysis of water erosion in the Bou Lajraf watershed by the PAP/RAC method, allowed to give results on the geomorphological situation of the surface at the level of water erosion. The predictive approach shows that 75% of the watershed has a high and very high erosive state. The fragility of materials and their sensitivity to water erosion are all the more important since most of the land is bare and directly exposed to the morphogenic effects of rainfall events. The appearance of sheet and linear water erosion forms in the upstream part of the watershed Bou Lajraf remains a morphogenic form and major soil degradation. This dynamic is detrimental to the local population, agricultural land and infrastructure. Analysis of the water erosion forms map shows that the Bou Lajraf watershed is influenced by a very high rate of slope degradation, with a large area of ​​badlands.